Thermal-Enhanced bri1-301 Instability Reveals a Plasma Membrane Protein Quality Control System in Plants - Lv, Minghui; Li, Meizhen; Chen, Weiyue; Wang, Yanze; Sun, Chao; Yin, Hongju; He, Kai; Li, Jia (Frontiers in Plant Science, 2018)
Brassinosteroids (BRs) are essential phytohormones mainly perceived by a single-pass transmembrane receptor-like protein kinase (RLK), BRASSINOSTEROID INSENSITIVE 1 (BRI1). bri1-5 and bri1-9, two distinct mutants with point mutations in the extracellular domain, show weak defective phenotypes. Previous studies indicated that bri1-5 and bri1-9 mutated proteins can be recognized and eliminated via an endoplasmic reticulum quality control (ERQC) mechanism. Most of these two proteins, therefore, cannot reach their destination, plasma membrane. Here we report our functional characterization of bri1-301, another BRI1 mutant protein with an amino acid substitution in the cytoplasmic kinase domain. bri1-301 is a partially functional BR receptor with significantly decreased protein abundance. Interestingly, protein stability and subcellular localization of bri1-301 are temperature-sensitive. At 22˚C, an optimal temperature for indoor Arabidopsis growth, bri1-301 shows a weak defective phenotype. At a lower temperature condition such as 18˚C, bri1-301 exhibits subtle morphological defects. At a higher temperature condition such as 28˚C, on the other hand, bri1-301 displays an extremely severe phenotype reminiscent to that of a null bri1 mutant due to greatly increased bri1-301 internalization and degradation. Our detailed analyses suggest that bri1-301 stability is controlled by ERQC and plasma membrane quality control (PMQC) systems. Since PMQC has not been well studied in plants, bri1-301 can be used as a model mutant for future genetic dissection of this critical progress.